Competitiveness, openness and economic growth - Mujica, Patricio (Estudios de Economía, 2016)
The purpose of this paper is to explore some issues and implications regarding the design of economic policies which derive from incorporating related to a society’s process of knowledge accumulation associated with an analysis of the relationship between economic growth and the level and composition of investment in knowledge. The paper develops a model which serves as an analytical frame to study the relationship between economic growth and knowledge and to examine the mechanism through which policies may alter the process of knowledge accumulation. It is concluded that the impact of the policies oriented to promote investment in human capital and technological research and development activities depends crucially on the characteristics of the knowledge generated. The policies to support education and technological research should: promote the development of the capacity to absorb new knowledge.